Immune mediators and therapies for pruritus in atopic dermatitis and psoriasis. Issue 1 (27th February 2019) - Yu, Sebastian; Li, Yanxi; Zhou, Yan; Follansbee, Taylor; Hwang, Samuel T.
Abstract: Atopic dermatitis (AD) and psoriasis (Pso) are two common inflammatory skin diseases which are symptomatically characterized by pruritus to variable degrees. Whereas AD is nearly always associated with pruritus, only 50%‐70% of patients with Pso suffer from itching. Within the last decade, the development of biologic agents targeting specific cytokines or cytokine receptors has led to tremendous progress in suppressing inflammation (and thus improving quality of life) in these two diseases. While suppressing inflammation would generally reduce pruritus in these inflammatory diseases, pruritus is still recalcitrant for treatment in some patients due to relative lack of therapeutics that specifically inhibit pruritus signaling. There is abundant evidence that certain cytokines and neuropeptides‐ion channels signaling mediate pruritus that is independent of inflammation in AD and psoriasis. Of note, Janus kinase (JAK) and nerve growth factor (NGF)‐tropomyosin receptor kinase A (TrkA)‐transient receptor potential vanilloid 1 (TRPV1) signaling partially regulates pruritus in AD and psoriasis. JAK kinases inhibitors decrease the extent of itch in patients with AD and psoriasis. In clinical trials, topical inhibitors of TrkA and TRPV1 have been reported to reduce pruritus in patients with Pso and AD, respectively. In this article, we review recent literature knowledge regarding the mechanisms underlying pruritus in AD and Pso, providing hypotheses for why pruritus may be more common in AD than in Pso. In light of the different mechanisms underlying these two diseases, the current and developing therapeutics, either in human clinical trials or animal studies, for targeting pruritus are also discussed. Abstract : Atopic dermatitis and psoriasis are two common inflammatory skin diseases which are characterized by pruritus. In this article, we review recent literature knowledge regarding the mechanisms underlying pruritus in atopic dermatitis and psoriasis, providing hypotheses for why pruritus may be more common in atopic dermatitis than in psoriasis.